Applications of DNA amplification techniques in veterinary diagnostics - Pfeffer, M. (Vet Res Commun, 1995)
An overview of the principles of the polymerase chain reaction, ligase chain reaction, self-sustained sequence replication and Qβ replicase is given. The application of these methods for the diagnosis of veterinary infectious and hereditary diseases as well as for other diagnostic purposes is discussed and comprehensive tables of reported assays are provided. Specific areas where these DNA-based amplification methods provide substantial advantages over traditional approaches are also highlighted. With regard to PCR-based assays for the detection of viral pathogens, this article is an update of a previous review by Belák and Ballagi-Pordány (1993).